2017
DOI: 10.2320/matertrans.m2016314
|View full text |Cite
|
Sign up to set email alerts
|

Effect of CaCO<sub>3</sub> Foaming Agent at Formation and Stabilization of Al-Based Foams Fabricated by Powder Compact Technique

Abstract: The paper presents the results obtained by in situ observation of Al-based foams formation at heating of powder compacts with calcium carbonate (CaCO 3 ) by comparing with those prepared with conventional titanium hydride (TiH 2 ). Foamable precursors comprising powder of either pure aluminium or AlZnMg-alloy were used for detailed investigation of foam evolution and stability. High temperature X-ray furnace was applied for in situ visualization of foam formation. It was identi ed that expansion and stability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 22 publications
0
6
1
1
Order By: Relevance
“…In this study, the optimal strength value of the foam was higher than the one reported by Michailidis et al [17] in which sugar and dissolution were applied as a foaming agent and foaming agent removal method, respectively. It is noteworthy that the optimal amount of strength value obtained in the present study is remarkably higher than those reported by other studies that worked on melting or dissolution route and other foaming agents such a polymer (PMMA), TiH 2 , and K 2 CO 3 [3,4,14,18]. This may possibly be the result of a higher amount in compacting pressure, as well as applying CaCO 3 as a foaming agent.…”
Section: Determination Of Linear Expansion Relative Density and Porcontrasting
confidence: 61%
See 3 more Smart Citations
“…In this study, the optimal strength value of the foam was higher than the one reported by Michailidis et al [17] in which sugar and dissolution were applied as a foaming agent and foaming agent removal method, respectively. It is noteworthy that the optimal amount of strength value obtained in the present study is remarkably higher than those reported by other studies that worked on melting or dissolution route and other foaming agents such a polymer (PMMA), TiH 2 , and K 2 CO 3 [3,4,14,18]. This may possibly be the result of a higher amount in compacting pressure, as well as applying CaCO 3 as a foaming agent.…”
Section: Determination Of Linear Expansion Relative Density and Porcontrasting
confidence: 61%
“…This was due to a higher diffusion, more interfaces between copper particles (low amount of foaming agent) during the solid-state sintering process and the higher strength of cell walls [15]. Figure 7(e) shows that the rise of compacting pressure from P2 to P5 (250 MPa to 624 MPa) upgrades the compressive strength of the samples from 324 MPa to 526 MPa because of the lower number of the pores and the strain hardening of copper particles [18]. When preform compacted below 250 MPa, the deficient bonding strength between Cu particles prompted the collapse of the green compact amid handling.…”
Section: Determination Of Linear Expansion Relative Density and Pormentioning
confidence: 98%
See 2 more Smart Citations
“…En algunas patentes tempranas (Nakamura et al, 2002) y en el trabajo reciente de Nakamura y colaboradores (Byakova, Nakamura et al, 2017) se encontró que el uso de CaCO 3 es potencialmente adecuado como agente espumante para la obtención de espumas mediante el método de fundición del metal base. Además, Bryat (Bryat et al;2008) informó que el CaCO 3 actúa como agente espumante cuando se encuentra en contacto con el aluminio en estado líquido y, al mismo tiempo, a través de los productos de descomposición tiene un efecto sobre la estabilidad de la espuma, permitiendo la formación de "espumas de aluminio autoestabilizadas".…”
Section: Introductionunclassified